The Effect of Aloe Vera Topical Gel Extraction on Tgf-Β1 Expression in Thermal Burn Eyelid Grade II Rats Model - Riani Erna; Kartini Wulan; Mgs. Irsan Saleh (Sriwijaya Journal of Medicine, 2022)
Grade II eyelid burns are burns that reach the epidermis and part of the dermis of the palpebrae and can have impaired wound healing. TGF β1 has the broadest spectrum of action, affecting all cell types involved in all stages of wound healing. TGF β1 increases rapidly after injury and reaches peak levels three days after injury, which coincides with the peak of the inflammatory phase of wound healing. Decreased expression of TGF β1 is associated with impaired wound healing. Aloe Vera has long been known in Indonesia as a healing plant. Aloe Vera extract contains a variety of bioactive compounds that play a role in stimulating wound healing. The administration of Aloe Vera extract on thermal burns aims to reduce inflammation, increase collagen content, and increase the rate of re-epithelization. The administration of Aloe Vera gel extract allows faster healing of thermal burns and rebuilds the vascularity of the wound tissue. Objective of this study is to determine the difference between the expression of Transforming Growth Factor Beta 1 (TGF β1) in a rat model of thermal burn injury grade II of the eyelids treated with topical Aloe Vera gel extract with the concentrations of 20%, 40%, Balanced Salt Sodium (BSS) and a control group that was not given burn intervention. An experimental study with the post-test-only approach with a control group design. 24 Rats have induced grade II eyelid thermal burns, divided into four groups: Normal (without treatment), negative control (BSS), given Aloe vera 20%, 40%. Then TGF β1expression was quantified using the Image J application. The Topical application of Aloe vera gel can increase the expression of TGF along with the increase in dose. The highest rise in TGF expression was found in the group with 40% Aloe vera gel, followed by 20% Aloe vera gel compared to the negative control (BSS Balanced Salt Solution). Aloe Vera can increase TGF expression in a rat model of grade II palpebral burn injury and is dose-dependent.